Penentuan Portofolio yang Optimal dengan Menggunakan Single Index Model pada Perusahaan Manufaktur yang Terdaftar di BEI - Mira Dwiastuti; Evaliati Amaniyah; Echsan Gani (BISMA (Bisnis dan Manajemen), 2018)
The purpose of study is to determinan optimal portofolio by using Single Index Model at manufacturing company in BEI. The method used in this study is descriptive method. By using purposive sampling method is obtained 11 sample of the manufacturing company. The result of this study  is only three company that make up the optimal portfolio from 11 company because they  have ERB more than cut off point (0,086198) and These companies are PT. Gudang Garam, TBk, PT Astra outopart Tbk dan PT. Unilever Indonesia Tbk.  The proportion of stock in the portfolio are 19.68% PT Gudang garam Tbk, 72.83%  PT Astra outopart Tbk and 7.49% PT. Unilever Indonesia Tbk.  The expected return portfolio is. 10.11% greater  than expected return risk free (SBI) that only 0.534%, risk portfolio 0.2261 smaller than some risk individual stock and beta portfolio 0.9342